PIEZO acts in an intestinal valve to regulate swallowing in C. elegans - Yeon-Ji Park; Jihye Yeon; Jihye Cho; Do-Young Kim; Xiaofei Bai; Yuna Oh; Jimin Kim; HoJin Nam; Hyeonjeong Hwang; Woojung Heo; Jinmahn Kim; Seoyoung Jun; et al. (Nature Publishing Group, 2024)
Sensations of the internal state of the body play crucial roles in regulating the physiological processes and maintaining homeostasis of an organism. However, our understanding of how internal signals are sensed, processed, and integrated to generate appropriate biological responses remains limited. Here, we show that the C. elegans PIEZO channel, encoded by pezo-1, regulates food movement in the intestine by detecting food accumulation in the anterior part of the intestinal lumen, thereby triggering rhythmical movement of the pharynx, referred to as the pharyngeal plunge. pezo-1 deletion mutants exhibit defects in the pharyngeal plunge, which is rescued by PEZO-1 or mouse PIEZO1 expression, but not by PIEZO2, in a single isolated non-neuronal tissue of the digestive tract, the pharyngeal-intestinal valve. Genetic ablation or optogenetic activation of this valve inhibits or induces the pharyngeal plunge, respectively. Moreover, pressure built in the anterior lumen of the intestine results in a pezo-1-dependent pharyngeal plunge, which is driven by head muscle contraction. These findings illustrate how interoceptive processes in a digestive organ regulate swallowing through the PIEZO channel, providing insights into how interoception coordinates ingestive processes in higher animals, including humans.